Interdisciplinary Rounds: A Significant Approach For Enhancing Doctor-Nurse Collaboration In Hospitals. A New Appraisal (Journal of Namibian Studies : History Politics Culture, 2022)
Interdisciplinary rounds (IDR) play a pivotal role in fostering collaboration between doctors and nurses within hospital settings. This structured approach brings together healthcare professionals from various disciplines to discuss patient cases, formulate care plans, and address complex medical issues. By facilitating comprehensive patient care, improving communication, and enhancing teamwork, IDR contributes to improved patient outcomes and increased satisfaction among healthcare providers. This article provides an overview of IDR, highlighting its significance, key components, and best practices for implementation.